Field Characterization of Landslide-Induced Surge Waves Based on Computational Fluid Dynamics - Wang, Rubin; Ding, Miangang; Wang, Yunzi; Xu, Weiya; Yan, Long (Frontiers in Physics, 2022)
Numerical simulation analysis of landslide-induced surge wave field characteristics offers great insights for engineering practices and is crucial for studying reservoir landslide disaster warning, prevention, and control. Based on computational fluid dynamics, this study established a numerical calculation model of a typical landslide surge to simulate and analyze the surge waves caused by the movement of a rigid landslide body along the slope and its propagation process. The results were compared with classical physical experiments to validate the applicability of the numerical model. Furthermore, effects of the shape and density of the landslide body on the surge wave generation, water entry characteristics of a landslide body, propagation pattern of surge waves were also studied. The results showed that: the starting position of the far-field landslide surge negatively correlated with the density of the landslide body; the shape of the landslide body did not substantially impact the far-field starting position, which was mainly influenced by the area of the water surface in contact with the sliding body. The research results provide important reference and technical support for reservoir landslide disaster warning, prevention, and control.